Pengaruh Current Ratio Dan Debit To Equity Ratio Terhadap Return On Assset Pada PT. Perkebunan Nusantara IV Periode 2016-2021 - Dharma, Budi; Suci, Indriani; Mahfadillah, Aninda (Universitas Labuhanbatu, 2022)
The purpose of this study was to examine the impact of Current Ratios and target capital Adequacy Ratios on PT’s Return on assets. Nusantara Plantation IV periode 2016-2021. Use of descriptive research methods and statistical analysis with multiple linear regression tests. The results of this study show that 39,1 % has a positive and significant impact on return on assets. Target capital Adequacy has a negative impact on return on assets, which is non significant at 30,3 %. At the same time, the Current ratio and the target capital Adequacy Ratio affect the Return on investment, with a large positive impact of 86,6 %.